Deep structure, long‐distance migration and admixture in the colour polymorphic land snail Cepaea nemoralis. (13th July 2022) - Ramos‐Gonzalez, Daniel; Saenko, Suzanne V.; Davison, Angus
Abstract: Although snails of the genus Cepaea have historically been important in studying colour polymorphism, an ongoing issue is that there is a lack of knowledge of the underlying genetics of the polymorphism, as well as an absence of genomic data to put findings in context. We, therefore, used phylogenomic methods to begin to investigate the post‐glacial history of Cepaea nemoralis, with a long‐term aim to understand the roles that selection and drift have in determining both European‐wide and local patterns of colour polymorphism. By combining prior and new mitochondrial DNA data from over 1500 individuals with ddRAD genomic data from representative individuals across Europe, we show that patterns of differentiation are primarily due to multiple deeply diverged populations of snails. Minimally, there is a widespread Central European population and additional diverged groups in Northern Spain, the Pyrenees, as well as likely Italy and South Eastern Europe. The genomic analysis showed that the present‐day snails in Ireland and possibly some other locations are likely descendants of admixture between snails from the Pyrenees and the Central European group, an observation that is consistent with prior inferences from mitochondrial DNA alone. The interpretation is that C. nemoralis may have arrived in Ireland via long‐distance migration from the Pyrenean region, subsequently admixing with arrivals from elsewhere. This work, therefore, provides a baseline expectation for future studies on the genetics of the colour polymorphism, as well as providing a comparator for similar species. Abstract : Population genomics of the colour polymorphic snail Cepaea neamoralis .